Big five personality traits and resilience as predictors for self-isolation adherence during COVID-19 pandemic - Kayvan Alimoradi; Reza Ghanei Gheshlagh; Ahmed Najeeb Albatineh; Bahram Nikkhoo; Farideh Nargesi; Khaled Rahmani (Tehran University of Medical Sciences, 2024)
Background & Aim: Results of previous studies on the role of personality traits and resilience in explaining health-oriented behaviors such as social/physical distance and self-isolation were inconsistent. The present study was conducted to determine the role of the five big personality traits and resilience in adherence to self-isolation during the COVID-19 pandemic. Methods & Materials: A prospective longitudinal cohort study tracked 112 healthcare providers who tested positive for SARS-CoV-2. Using GPS data from their cell phones, researchers assessed self-isolation adherence over 14 days. Participants completed NEO-Five-Factor Inventory (NEO-FFI) and Connor-Davidson Resilience Scale (CD-RISC) questionnaires. Results: Sixty-one (58.7%) of the subjects violated their self-isolation, and 43 (41.3%) did not violate it during the 14 days after PCR positivity for COVID-19. After adjustment for potential confounders, results showed that only two of the five big personality traits included, conscientiousness (AOR=1.37; 95%CI: 1.15-1.63) and neuroticism (AOR=0.85; 95%CI: 0.74-0.98), were significantly related to the self-isolation adherence. This means a one-unit increase in conscientiousness is associated with 37% higher odds of self-isolation adherence, while a one-unit increase in neuroticism reduces self-isolation adherence by 15%.  Resilience was the main predictor for self-isolation adherence in which a one-unit increase in resilience score, the odds of adherence to self-isolation significantly increased by 18% (AOR=1.18, 95%CI: 1.07-1.30) (P<0.001). Conclusion: The study suggests that fostering conscientiousness and resilience among individuals may enhance self-isolation commitment during pandemics. Further research is needed to explore the influence of agreeableness, extraversion, and openness to experience on self-isolation adherence.